Islam, Radicalism, Democracy, and Global Trends in Southeast Asia - Fadlan, Muhammad Nida'; Saputra, Rangga Eka (Studia Islamika, 2017)
In the last few years, we have witnessed tremendous events occurred on social, religious and political fields in Southeast Asia. This region is believed to be one the most hybrid regions in the world. On one hand, we see the proliferation of democracy and civil society in most of Southeast Asian countries. On the other hand, we also see religious extremism, terrorism, ethno-religious conflicts, and other religious-based violence which have disrupted the stability of this region. The Marawi conflict in the Philippines, the Rohingya case in Myanmar, as well as several cases of violence against minorities in Indonesia and several other Southeast Asian countries are clear evidence that this problem poses threats to the stability of this highly plural societies in the region. For the reason above, the Center for the Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University (UIN) Jakarta held the 2nd Studia Islamika International Conference 2017 with the main theme "Southeast Asian Islam: Religious Radicalism, Democracy and Global Trends" on 8-10 August 2017 in Jakarta, Indonesia. This conference is a continuation of the first conference held in 2014.The 2nd Studia Islamika International Conference 2017 is organized to respond various aspects related to current social and religious issues in Southeast Asia. The conference explores Southeast Asian's political trends including religious radicalism, democratic development, and global trends. In addition, the conference is also dedicated to promote Studia Islamika, published by PPIM, as an important reference on studies of Islam in Indonesia and Southeast Asia.DOI:Â 10.15408/sdi.v24i3.6566